Sergey Yesenin in the World of Armenian Poets - JANPOLADYAN, MAGDA (Bulletin of Yerevan University H: Russian Philology, 2021)
The article covers and characterizes the perception of Sergey Yesenin as “the most Russian poet” by different generations of Armenian poets. Different memoirs, articles and poems, devoted to Sergey Yesenin, show why his poetry was so familiar and liked by Armenian poets. The works disclosed the brightest and most defining features of Yesenin’s lyrics, as well as the influence he had on certain Armenian poets. This article also features translations of several works by Yesenin and his Armenian editions.